In Silico Analysis of Untranslated Region 5’ and 3’ of Dengue Virus for mRNA Vaccine Development - Safrullah, Muhamad Iqbal; Dewi, Beti Ernawati; Sjatha, Fithriyah (Universitas Brawijaya, 2025)
Dengue fever is mosquito-borne viral infection that occur widely in tropical and sub-tropical area. With limited vaccine against dengue virus (DENV) available, the development of DENV mRNA vaccine is promising future for disease control. This study provides an in-depth in silico analysis of the 5’ and 3’ untranslated regions (UTRs) of the DENV genome. These regions play critical roles in viral protein translation and replication, and may serve as valuable targets for optimizing mRNA vaccine design. In this study, we comparing the nucleotide composition, secondary structure stability, and structural features of DENV UTRs across all four serotypes representative with those of Pfizer’s UTRs, aiming to identify key differences that could be utilise in the development of DENV mRNA vaccine design. From computational secondary structure, we can see some essential structure in DENV UTR, like S1 for ribosomal recognition, CS for genome cyclization. Methods involved computational analysis of nucleotide content (GC and AT percentages), secondary structure prediction, and thermodynamic stability assessment using Gibbs free energy (?G) calculations. The results revealed that DENV UTRs are highly conserved and structurally complex with higher GC content in the 5’ UTRs contributing to increased stability and potential impact on translation efficiency. DENV UTRs also exhibited more negative ?G values, indicating greater thermodynamic stability compared to Pfizer UTRs. The study concludes that understanding these structural and compositional differences can guide the rational design of mRNA vaccines, enhancing antigen expression. Future research should focus on functional validation of engineered UTRs to improve vaccine efficacy and safety, leveraging the insights gained from these structural analysis.